2019
DOI: 10.1242/jcs.228007
|View full text |Cite
|
Sign up to set email alerts
|

The integral function of the endocytic recycling compartment is regulated by RFFL-mediated ubiquitylation of Rab11 effectors

Abstract: Endocytic trafficking is regulated by ubiquitylation (also known as ubiquitination) of cargoes and endocytic machineries. The role of ubiquitylation in lysosomal delivery has been well documented, but its role in the recycling pathway is largely unknown. Here, we report that the ubiquitin (Ub) ligase RFFL regulates ubiquitylation of endocytic recycling regulators. An RFFL dominant-negative (DN) mutant induced clustering of endocytic recycling compartments (ERCs) and delayed endocytic cargo recycling without af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 95 publications
(129 reference statements)
2
19
0
Order By: Relevance
“…The molecular rheostat function based on the fine titration of the ubiquitination by the cooperative action of a ubiquitin (Ub) ligase and a deubiquitinating enzyme (DUB) has been demonstrated in the actin-assembly function of the WASH complex at EEs (Hao et al, 2015). A recent study demonstrated that ubiquitination by multiple Ub ligases and interaction with several DUBs also regulates ERC dynamics (Sakai et al, 2019). Inhibition of an Ub ligase that acts at the ERC (Sakai et al, 2019) or its over-expression (Coumailleau et al, 2004) impairs the segregation of EEs and the ERC, inhibits ERC-to-TGN trafficking, and redistributes a TGN resident protein (TGN46) into the ERC.…”
Section: Targeting the General Mechanism Of Host-cell Factors Membranmentioning
confidence: 99%
See 2 more Smart Citations
“…The molecular rheostat function based on the fine titration of the ubiquitination by the cooperative action of a ubiquitin (Ub) ligase and a deubiquitinating enzyme (DUB) has been demonstrated in the actin-assembly function of the WASH complex at EEs (Hao et al, 2015). A recent study demonstrated that ubiquitination by multiple Ub ligases and interaction with several DUBs also regulates ERC dynamics (Sakai et al, 2019). Inhibition of an Ub ligase that acts at the ERC (Sakai et al, 2019) or its over-expression (Coumailleau et al, 2004) impairs the segregation of EEs and the ERC, inhibits ERC-to-TGN trafficking, and redistributes a TGN resident protein (TGN46) into the ERC.…”
Section: Targeting the General Mechanism Of Host-cell Factors Membranmentioning
confidence: 99%
“…A recent study demonstrated that ubiquitination by multiple Ub ligases and interaction with several DUBs also regulates ERC dynamics (Sakai et al, 2019). Inhibition of an Ub ligase that acts at the ERC (Sakai et al, 2019) or its over-expression (Coumailleau et al, 2004) impairs the segregation of EEs and the ERC, inhibits ERC-to-TGN trafficking, and redistributes a TGN resident protein (TGN46) into the ERC. Spatiotemporal regulation of ubiquitination of host-cell factors that control endosomal tubulation (i.e., EHD1 and MICAL-L1) has been proposed to be essential for segregation of EE and the ERC (Sakai et al, 2019).…”
Section: Targeting the General Mechanism Of Host-cell Factors Membranmentioning
confidence: 99%
See 1 more Smart Citation
“…RFFL has a Fab-1, YGL023, Vps27, and EEA1 (FYVE)-like domain that binds to phosphatidylinositol (PI) 3-phosphate (PI(3)P) and PI(5)P in the N-terminal region, the Really Interesting New Gene (RING) domain which is important for ubiquitin ligase activity in the C-terminal region, and multiple disordered regions within other regions [48]. RFFL does not have a transmembrane domain, but its N-terminal domain is palmitoylated and is localized on the cytoplasmic side of the plasma and endosomal membranes [49,50]. RFFL directly recognizes the NBD1 of CFTR through the N-terminal disordered regions.…”
Section: Cystic Fibrosis Transmembrane Conductance Regulator (Cftr) Pmentioning
confidence: 99%
“…Of the other proteins present, Rab11 is considered a marker but is also present in early endosomes and multivesicular bodies (review [21,25,26]). The early endosomal markers, Rab5 and EEA1, and late endosomal markers, Rab7 and Lamp1, accumulate in the ERC [27]. The significance of our findings is that one conformation of PKC, thought to include the enzymatically active molecules, is processed to another during endosomal trafficking.…”
Section: Does Pkc Regulate Egfr Traffic?mentioning
confidence: 56%